Teaching Celia in the Age of Black Lives Matter - Byrd, Brandon R. (Radical Teacher, 2016)
The emergence of Black Lives Matter has introduced a language of black liberation to a new generation of students. In doing so, it has provided an opportunity for historical study. Teacher-scholars can and should take advantage of the renewed interest in systemic threats to black life in the United States when teaching about past victims of state-sanctioned violence including Celia, an enslaved teenager executed for killing her master after years of sexual abuse. In doing so, they can not only draw useful connections between the past and present but also lay the foundations for a more meaningful study of black radicalism and black resistance in the United States.